Effect of Time Between Carbon Dioxide Treatments on the Onset of Oviposition in Queen Honey Bees - Gąbka Jakub; Gąbka Joanna; Zajdel Barbara (Journal of Apicultural Science, 2022)
It is commonly known that two carbon dioxide treatments accelerate the beginning of egg laying in honey bee queens. However, the minimum time between anaesthesias needed for ovary activation has not yet been examined. The aim of the study was to investigate the effect of time between carbon dioxide treatments on the onset of oviposition in instrumentally inseminated and virgin queen honey bees. About half of the queens were anaesthetised before insemination and a second time during insemination, and the rest of the queens were anaesthetised two times without insemination. The time between carbon dioxide treatments was as follows: 96, 48, 24, 12, 6, 3 hrs, 10 min, 5–6 sec. Queens in a control group were anaesthetised only once. The mean number of days between the second treatment and the onset of oviposition in particular groups and in the control group was 10.3, 7.6, 9.9, 10.5, 7.8, 10.9, 14.2, 15 and 21.9, respectively, and the median was 9, 7, 7, 8, 7, 8.5, 11.5, 13 and 21 days, respectively. Queens in groups 5–6 sec and 10 min began oviposition significantly earlier than those in control group, but significantly later than in groups from 3 to 96 hrs. Instrumentally inseminated queens started to lay eggs at the same time (mean 12 and median 9 days after second treatment) as queens treated with carbon dioxide without insemination (mean 11.7 and median 9 days).